Thomas Hutchinson and the Origins of the American Revolution. - Walmsley, Andrew Stephen (American social experience series., 1998)
Rarely in American history has a political figure been so pilloried and despised as Thomas Hutchinson, Governor of Massachusetts and an ardent loyalist of the Crown in the days leading up to the American revolution. In this narrative and analytic life of Hutchinson, the first since Bernard Bailyn's Pulitzer-Prize-winning biography a quarter century ago, Andrew Stephen Walmsley traces Hutchinson's decline from well- respected member of Boston's governing class to America's leading object of revolutionary animus. Walmsley argues that Hutchinson, rather than simply a victim of his inability to un.